2010
DOI: 10.1136/bjo.2009.173187
|View full text |Cite
|
Sign up to set email alerts
|

Family history, near work, outdoor activity, and myopia in Singapore Chinese preschool children

Abstract: Aims To investigate the risk factors for myopia, including near work and outdoor activity, in Singapore Chinese preschool children. Methods A cross-sectional study, with disproportionate random sampling by 6-month age groups, of 3009 Singapore Chinese children aged 6–72 months was performed. Information on family history, near work and outdoor activity was obtained. Spherical equivalent refraction (SEA) was assessed. Results Children with two myopic parents were more likely to be myopic (adjusted OR=1.91; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
142
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(158 citation statements)
references
References 20 publications
(29 reference statements)
15
142
1
Order By: Relevance
“…Similarly, some previous studies among Chinese children also showed that there was no significant association or weak association between outdoor activity and myopia. 7,[37][38][39] The different results may be related to 40,41 Consistent with previous findings showing that parental myopia was significantly related to myopia, and illustrating an increased risk of myopia in children with increasing numbers of myopic parents, 13,17,24,28 the current study demonstrated that there was a trend for higher myopia prevalence among children with a parental myopia history. Both male and female students with one myopic parent or two myopic parents were at a higher risk of myopia than those without myopic parents.…”
supporting
confidence: 89%
“…Similarly, some previous studies among Chinese children also showed that there was no significant association or weak association between outdoor activity and myopia. 7,[37][38][39] The different results may be related to 40,41 Consistent with previous findings showing that parental myopia was significantly related to myopia, and illustrating an increased risk of myopia in children with increasing numbers of myopic parents, 13,17,24,28 the current study demonstrated that there was a trend for higher myopia prevalence among children with a parental myopia history. Both male and female students with one myopic parent or two myopic parents were at a higher risk of myopia than those without myopic parents.…”
supporting
confidence: 89%
“…Following this review, a number of manuscripts were excluded due to information, including outcome, the exposure of interest or essential data, being omitted. A total of 16 studies were eligible for final inclusion (12)(13)(14)(15)(16)(17)(26)(27)(28)(29)(30)(31)(32)(33)(34). Of these, six were prospective cohort (12,13,15,17,31,32), eight were cross-sectional (14,16,(26)(27)(28)(29)(30)35) and two were case-control studies (33,34).…”
Section: Methodsmentioning
confidence: 99%
“…However, there are large inconsistencies in the odds ratios (ORs) among these studies (ranging from 1.48 to 7.90). Furthermore, other studies have identified no statistically significant association between parental myopia and a child's risk of developing myopia (15)(16)(17). These contrasting conclusions may be due to differences in the study designs.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations